Synergetic Effect of Mo, Mg-Modified Sn-β Over Moderate-Temperature Conversion of Hexose to Alkyl Lactate - Hu, Yanru; Zhang, Gengrui; Liu, Lele; Chi, ZiXin; Wang, Shuai; Lin, Jingdong; Xiong, Haifeng; Wan, Shaolong (Frontiers in Chemistry, 2022)
The thermocatalytic conversion of hexose into valuable chemicals such as methyl lactate under mild conditions is very appealing. Here, we report that Mo, Mg co-modified Sn-β catalyst can effectively catalyze the transformation of glucose and fructose into alkyl lactate at moderate temperatures. A maximum yield of around 35% of methyl lactate was achieved from the conversion of glucose in methanol at 100°C over Sn-β catalyst modified with 3 wt% Mo and 0.5 wt% Mg. However, up to 82.8% yield of ethyl lactate was obtained in the case of fructose in ethanol upon the same catalytic condition, suggesting a significant solvent effect. The Mo species plays a key role to enable the retro-aldol condensation of fructose, in which the competing side reactions are significantly suppressed with the assistance of neighboring Mg species probably through a synergetic effect of Lewis acid-base.